Strengthening the digital community space and English village initiative for sustainable smart village development in Bumi Harjo - Almustari A. Enteding; Nadya Septiani Rahman; Muhlin; Yuliana Mangendre; Nurlaela (University of Merdeka Malang, 2026)
This community service program aimed to empowering the Village Digital Community Space (RKDD) and developing Digital-English Villages. Conducted in Bumi Harjo Village, Moilong District, Banggai Regency, Central Sulawesi, over an eight-month period, this program addressed the issue of local RKDD which has not been running optimally. As it tends to limit its function as an administrative facilitator with the absence of sustainable digital literacy improvement activities. The implementation method uses the Participatory Action Research (PAR) approach by involving the village government, 10 RKDD managers as the primary target, academics from Tompotika Luwuk University, and the local community. Evaluation was conducted through pre-and post-activity competency assessments and satisfaction surveys. Activities include socialization, preparation of roadmaps, training, mentoring, and development of the